Quantification and Comparison of Opium (Morphine) and Tramadol from Biological Samples "Liquid - Liquid Extraction" - M.A. Shihata, Ahmed; ELESSAWY, A.M.; M. Elanwer, Alaa (Journal of New Developments in Chemistry, 2020)
Two analgesic were determined opium (morphine) and tramadol and comparison between two methods of extractions from biological samples. Opium and its derivatives and tramadol are the most commonly used medications for treatment of acute and chronic pain. opium was used as a sedative and hypnotic, but it was determined to be addictive and tramadol prescribed narcotic analgesic; main metabolite of opium is morphine and tramadol overdose was reported old male 40 years. Morphine and tramadol isolated by two methods of extraction, Stas Otto and ammonium sulfate extraction from liver tissues and comparison between efficiency of the two methods. Liver extractions have morphine and tramadol was quantified by GC-MS. Morphine was determined in liver concentration 176 u/g in Stas Otto. Liver concentration of morphine 267 u/g in ammonium sulfate extraction. Tramadol was determined in liver concentration 26.18 u/g in Stas Otto. Liver concentration of tramadol 22.41 u/g in ammonium sulfate extraction.
Keywords: Morphine; Tramadol; Extraction; GC-MS.